Economic impacts of marine ecological change: Review and recent contributions of the VECTORS project on European marine waters. (5th February 2018) - Groeneveld, Rolf A.; Bartelings, Heleen; Börger, Tobias; Bosello, Francesco; Buisman, Erik; Delpiazzo, Elisa; Eboli, Fabio; Fernandes, Jose A.; Hamon, Katell G.; Hattam, Caroline; Loureiro, Maria; Nunes, Paulo A.L.D.; et al.
Abstract: Marine ecological change is likely to have serious potential economic consequences for coastal economies all over the world. This article reviews the current literature on the economic impacts of marine ecological change, as well as a number of recent contributions to this literature carried out under the VECTORS project. We focus on three main types of change, namely invasive alien species; outbreak-forming species, such as jellyfish and toxic algae; and gradual changes in species distribution and productivity. The case studies available in the literature demonstrate that the impacts of invasions and outbreaks on fisheries, aquaculture, and tourism can potentially amount to several tens of millions of dollars each year in some regions. Moreover, stated preference studies suggest a substantial impact on coastal tourism and non-use values that is likely not visible in case studies of specific outbreak events. Climate-driven gradual changes in distribution and productivity of commercial fish stocks will have an impact on fisheries, although these impacts are likely to be overshadowed by much larger changes in prices of seafood and fuel. Highlights: We review the literature on the economic impact of marine ecological change. Case studies of invasions and outbreak events show impacts on fisheries and tourism. Stated preference studies add insights into tourist behaviour and nonuse values. Fuel and fish price changes have larger impact than climate-driven gradual changes. Economic analyses of regional impacts and policy measures are needed.